Mātauranga Māori driving innovation in the New Zealand scampi fishery. Issue 4 (2nd October 2018) - Ogilvie, Shaun; Major, Robert; McCarthy, Alaric; Paine, Glenice; Paine, Richard; Connor, Geoff; Connor, Steve; Taylor, David; Jeffs, Andrew; Heasman, Kevin; Batstone, Chris; Chambers, Benita; et al.
ABSTRACT: Motivation to improve commercial fishing technology is changing from 'how can we catch more fish' to 'how can we reduce the impact of fishing on the environment'. To implement new fisheries technologies and innovations, it is important to have sources of innovative ideas for improvement, and processes to allow the uptake and transition from old to new technologies. One fishery that is undergoing a technology transition is the New Zealand scampi ( Metanephrops challengeri ) fishery. Here we report on a research programme aimed at improving the cultural and environmental performance of scampi fishing practices, initiated by the Māori-owned Waikawa Fishing Company, and underpinned by Mātauranga Māori and values inherent in kaitiakitanga. This paper provides a case study for how Mātauranga Māori and western science can engage in a fisheries technology transition through a transdisciplinary research programme.